Environmental conditions, mobility and history of contact as determinants of dengue haemorrhagic fever in Denpasar, 2012 - Kenyem Subagia; Anak Agung Sagung Sawitri; Dewa Nyoman Wirawan (Universitas Udayana, 2013)
Bali Province is endemic for Dengue Hemorrhagic Fever (DHF). Denpasar is reported to have the highest cases with incidence rates of 143.2 per 100.000 persons in 2011. Vaccine has not been available until recently and efforts to control the endemic are only achieved modest result. This case control study was aimed to identify risk factors for high incidence rate of DHF in Denpasar. Total cases were 80 and controls were 160 persons. The variables explored were characteristics of the respondents, indoor and outdoor environtment, respondent mobility, history of contact with the DHF patients and larvae presence in public places with a maximum radius of 100 m from respondent’s residence. The data were collected from documents, interviews and observations. The instruments used were questionnaires and check lists. Data analysis was carried out using univariate, bivariate (chi-square) and multivariate (logistic regression) analysis. Bivariate analysis showed several factors which increase the risk of dengue incidence in Denpasar: age OR=1.88 [95%CI: 1.09-3.23], indoor condition OR=8.27 [95%CI: 2.63-26.07], mobility OR=2.78 [95%CI: 1.57-4.92] and contact history OR=2.85 [95%CI: 1.62-5.03]. After multivariate analysis, the variables that contributed to increase the risk of DHF incidence in Denpasar were age OR=1.09 [95%CI: 1.06-1.11], indoor environment condition OR=10.74 [95%CI: 2.94-39.32], respondent mobility OR=3.12 [95%CI: 1.55-6.28] and history of contact OR=2.4 [95%CI: 1.21-4.79]. Health promotion need to be improved to prevent DHF by increasing indoor environmental quality including intervention to refregerator drainage and residual water tapping at dispenser